2019
DOI: 10.1111/odi.13110
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mitophagy in inflamed odontoblasts

Abstract: Objectives Mitophagy is an important mitochondrial quality control mechanism. In this study, we investigated the mitochondrial damage and mitophagy occurred in inflammatory human dental pulp and lipopolysaccharide‐stimulated preodontoblasts. Materials and Methods In dental pulp tissues and lipopolysaccharide‐stimulated preodontoblasts, immunofluorescences and Western blot were performed to detect the expression of mitochondrial and mitophagy‐related proteins, and autophagy markers were also examined. Reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…In our previous study, we found that autophagy was activated to regulate odontoblast differentiation [31] and that Parkin-dependent mitophagy was activated to degrade impaired mitochondria in LPS-induced odontoblasts [21]. Several studies have shown that the accumulation of abnormal mitochondria and cytoplasmic transport of mtDNA are activated by the consumption of autophagic proteins, which depend on the NALP3 inflammasome and mtROS [32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous study, we found that autophagy was activated to regulate odontoblast differentiation [31] and that Parkin-dependent mitophagy was activated to degrade impaired mitochondria in LPS-induced odontoblasts [21]. Several studies have shown that the accumulation of abnormal mitochondria and cytoplasmic transport of mtDNA are activated by the consumption of autophagic proteins, which depend on the NALP3 inflammasome and mtROS [32].…”
Section: Discussionmentioning
confidence: 98%
“…The carious teeth group consisted of teeth collected from patients diagnosed with caries and carious lesions but without any history of spontaneous pain. The pulpitis group consisted of teeth collected from patients diagnosed with irreversible pulpitis with spontaneous pain, heat-or cold-stimulating pain and pain at night [21,22].…”
Section: Human Dental Pulp Samplesmentioning
confidence: 99%
“…2018, Yang et al . 2019), and the release of cytokines (Chung et al . 2019) via the induction of the NF‐κB pathway (Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…2003), whereas, in pathological incidents, the dynamic is shifted towards mitochondrial fission (Yang et al . 2019); whether uncontrolled, this excessive fission leads to cellular apoptosis. Aside from proteins controlling the mitochondria, Bcl‐2 and Bax, anti‐apoptotic and pro‐apoptotic proteins, respectively, are important proteins that regulate cell apoptosis by modifying the mitochondrial membrane (Salakou et al .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence implicate that autophagy involves in the pathology of pulpitis (Table 2). Autophagy and mitophagy are significantly upregulated in caries and inflammatory dental pulp samples 72,73 . In irreversible pulpitis rat model, autophagy occurs in a manner that is consistent with the progression of pulpitis 74 .…”
Section: Pathological Roles Of Autophagy In Toothmentioning
confidence: 91%